Social dimension of access, use and appropriation of the CIT - Crovi-Drueta, Delia (2008)
This article to analyzing three concepts related to the digital divide: access, use, and appropriation. Seeks to place her analysis in a broader context than the one defined by the technological infrastructure, taking her thoughts to the social and cultural environment. For these purpose, she first finds what circumstances are the ones that bring to life the information society and its insertion in Latin America paradigms. Then she analyzes the concepts mentioned before and pose the need to do an education on a digital culture that takes into account the educational, cognitive and socioeconomics elements that define it.